PENGARUH MEDIA KOMECA TENTANG POLA MAKAN SEHAT TERHADAP PENGETAHUAN REMAJA SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS - Gustyana, Nandini Dwi; Rosita, Neng Ayu (Jurnal Kesehatan Siliwangi, 2024)
Background: Cases of diabetes mellitus are on the rise; in Cimahi city, there were 7,604 in 2019 and 10,640 in 2020, according to the CimahiCity Health Office (2022). Not only does this substantial rise occur in the elderly, but it is also seen in teenagers. According to Goran et al. (2003), a significant portion of overweight teenagers (more than 25%) develop diabetic symptoms by the time they reach the age of 15. The goal of this study is to assess the impact of KOMECA media on healthy eating habits among SMPN 12 Cimahi teenagers in relation to their awareness of diabetes mellitus prevention initiatives. Method: This study used a quantitative approach based on a pre-experimental design, especially a one-group pretest-posttest layout. Professional simple random sampling, a method of probability sampling, was used to choose the sample. The Wilcoxon test was used to analyze the data. Also, the 4D model was used for media creation. Results: The average level of knowledge among students rose from 55.54 to 83.84 after being exposed to the KOMECA (Kotak Inviting Reading) media.Conclusion: After receiving the KOMECA (Kotak Inviting Reading) media, there was a 51% increase in awareness about the importance of good eating habits in preventing diabetes mellitus.